Atmospheric Pressure Plasma Treatment of Nylon 6, 6 and Polyester Fabrics for Enhancing Antistatic Properties. Issue 4 (July 2016) - Dincmen, Melek Gul; Hauser, Peter J.; Gursoy, Nevin Cigdem
In this study, antistatic properties of nylon 6, 6 and polyester fabrics were improved. Diallyldimethylammonium chloride (DADMAC) monomer was used as an antistatic agent together with di(ethylene glycol) diacrylate crosslinker. Non-thermal, high density atmospheric pressure plasma was used to graft and polymerize the monomer/crosslinker layer on the fabric. Surface resistivity and electrostatic charge generation/dissipation of fabrics were measured after Soxhlet extraction with water and after home laundering. All fabrics were stained with C.I. Direct Red 80 to confirm the newly grafted polyDADMAC layer on the fabric and UV-Visible spectroscopic analyses were carried out on dye baths. Results showed that the grafted polyDADMAC layer was still present after water Soxhlet extraction and after home laundering. The antistatic performance of the fabrics was greatly improved with the treatment.